Exploration of the views of healthcare professionals working in a mental health trust in England on pharmacists as future approved clinicians: early findings. (26th March 2021) - Adam, B; Keers, R N
Abstract: Introduction: The 2007 amendment to the Mental Health Act (MHA) 1983 enabled various non-medical professionals to now qualify as approved clinicians (ACs); these included social workers, mental health and learning disability nurses, clinical psychologists and occupational therapists. [1–2] As ACs, these professionals can take on roles of clinical leadership whilst assuming responsibility for patients under the Act. Although mental health pharmacists have recognised specialist clinical roles and regularly work alongside these professionals in caring for patients, they are not presently permitted to practise as ACs. Aim: This study sets out to investigate the views of healthcare professionals working in a mental health trust in England on this hitherto unexplored group of the mental health workforce as potential ACs. Methods: Upon obtaining ethics approval, pharmacists, ACs and other experienced mental health professionals working in one mental health trust in England were approached via internal trust email to take part in a digitally audio recorded semi-structured interview to explore their views on pharmacists as potential ACs in future. A thematic analysis is being performed on the entire set of transcripts and an additional sentiment analysis will be applied to specific parts of the dataset. Results: A total of 11 interviews were completed with 6 pharmacists, 4 medical ACs and 1 'other' mental health professional thus far, with recruitment ongoing. Emerging themes included wide recognition among participants of highly valued key skills of pharmacists within mental health services provision, for instance their ability to access and appraise specialist literature as well as their analytical skills to apply expert knowledge to real-life cases. Participants identified unique challenges to pharmacists potentially becoming ACs in future, namely the traditional organisational structures whereby pharmacists are line managed and clinically supervised from within a pharmacy department which sits external to the clinical teams they typically work in, and the lack of pharmacists being fully embedded in interdisciplinary teams. Conclusion: Since this is the first study of its kind to be conducted on a small cohort of participants working within one mental health trust in England, this qualitative study will likely highlight the need for further research to be carried out on the topic, such as data collection in several other NHS trusts as well as recruiting participants from the working group and other stakeholders involved in the most recent amendment of the Act. Whilst data collection and analysis are ongoing, initial findings help shed light on potential barriers and also possible solutions to these, as well as other opportunities for pharmacists wishing to assume higher leadership roles within mental health services in England. References: 1. Barcham, C. Understanding The Mental Health Act Changes – Challenges And Opportunities For Doctors. BJMP. 2008;1 (2):13–17. 2. Oates, J., Brandon, T., Burrell, C., Ebrahim, S., Taylor, J. & Veitch, P. Non-medical approved clinicians: Results of a first national survey in England and Wales. International Journal of Law and Psychiatry . 2018;60:51–56.